Climate Services for Resilient Development (CSRD) in South Asia - Khan, Shahidul Haque (2017)
Climate Services for Resilient Development (CSRD) is a global partnership that connects climate and environmental science with data streams to generate decision support tools and training for decision-makers in developing countries. Translating complex climate information into easy to understand actionable formats to spread awareness in the form of climate services is core to CSRD’s mission. CSRD works across South Asia (with emphasis on Bangladesh), the Horn of Africa (Ethiopia), and in South America (Colombia) to generate and provide timely and useful climate information, decision tools and services. In South Asia, CSRD focusses the development, supply and adaptation of agricultural climate services to reduce vulnerability by increasing resiliency in smallholder farming systems, which is strategically aligned with the Global Framework for Climate Services.